RESISTING TRANSNATIONAL REPRESSION: THE DIGITAL SECURITY PRACTICES OF DIASPORA AND EXILED HUMAN RIGHTS DEFENDERS - Michaelsen, Marcus (AoIR Selected Papers of Internet Research, 2020)
For diaspora activists in transnational networks, digital media play a crucial role to mobilize and advocate against authoritarian regimes in their country of origin. Yet the reliance on these technologies creates multiple points of exposure that state actors exploit to silence and punish dissent from abroad. While research has exposed the technical underpinnings of digital attacks targeting civil society, less is known on how potential targets perceive and respond to these threats. Using more than 50 interviews with exiled human rights defenders and journalists from Egypt, Syria and Iran, this paper investigates risk perceptions and security practices of activists in transnational networks. It shows that rather than on nuanced risk assessment, digital security decisions and behavior are often built on the “imagined affordances” of digital technologies for surveillance and information control. The paper argues that the complexity of digital tools and constantly evolving risks thus only work to aggravate activists’ uncertainty regarding the capabilities of the state actors threatening them, reinforcing the silencing effects of transnational repression. Networks of incident response, support and information sharing, in turn, will help to strengthen the digital resilience of transnational civil society.